Forging Ethiopia’s Food Future through its Groundbreaking National Agroecology Strategy - Balcha, Yodit; Teferi, Zenebe Adimassu; Woldemeskel, Endalkachew; Degefie, Degefie Tibebe; Mitiku Ayele; Ali Mohammed; Mockshell, Jonathan Yaw; Geck, Matthias; Araujo De Lima, Silvia (2025)
A newly developed Ethiopian National Agroecology Strategy (ENAS) aims to establish a more equitable, resilient, and sustainable agricultural system. Led by the Ethiopian Ministry of Agriculture with support from the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), and the Center for International Forest Research - World Agroforestry (CIFOR-ICRAF), ENAS addresses urgent challenges, including land degradation, climate vulnerability, and persistent food insecurity. It has been co-developed through extensive stakeholder consultations and aligns with both national priorities and continental and global frameworks. The Strategy embraces six Strategic Objectives and 26 Strategic Focus Areas in a comprehensive Implementation Matrix. Ethiopia plans to validate, publish, and launch ENAS by February 2026, positioning agroecology as a national movement to restore ecosystems, strengthen livelihoods, and build a climate-resilient food future.